EFFECTS OF LIVE BODY WEIGHT AND LEPTIN CONCENTRATION ON IRAQI CHICKENS FERTILITY AND HATCHABILITY - Mohammed H. Hamad,; Waleed Kh. A. Al – Hayani,; Firas M.Hussein, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This Study was conducted out at the Ministry of Agriculture's Poultry Research Station/Animal Resources Department/Agricultural Research Center. To see how body weight (BW) and leptin hormone (LEP) levels in breeder blood affect fertility and hatchability. 140 Iraqi local laying chickens (120 females + 20 males) aged 28 weeks were used in the study. Following the numbering of females, the birds were grown in individual cages and dispersed sequentially on cages. The experiment was divided into three periods, each lasting 28 days, during which the breeder's live body weight was recorded and divided into two categories (greater than 1.5 kg and less than 1.5 kg), and blood samples were collected at the end of each period to determine the concentration of leptin hormone in the breeders' blood. For comparison between mothers' performance, hormone concentration is separated into three groups: high, medium, and low. The percentage of fertile eggs (FE), the percentage of hatched chicks from total eggs (HAT), the percentage of hatched chicks from fertile eggs (HAF), and the percentage of mortality (MO) all showed a significant increase (p